Metalation of 2HTCNPP on Ag(111) with Zn: Evidence for the Sitting atop Complex at Room Temperature - Kuliga, Jan (Chemphyschem, 2021)
We study the interaction and metalation reaction of a free base 5,10,15,20‐terakis(4‐cyanophenyl)porphyrin (2HTCNPP) with post‐deposited Zn atoms and the targeted reaction product Zn‐5,10,15,20‐terakis(4‐cyanophenyl)porphyrin (ZnTCNPP) on a Ag(111) surface. The investigations are performed with scanning tunneling microscopy at room temperature after Zn deposition and subsequent heating. The goal is to obtain further insights in the metalation reaction and the influence of the cyanogroups on this reaction. The interaction of 2HTCNPP with post‐deposited Zn leads to the formation of three different 2D ordered island types that coexist on the surface. All contain a new species with a bright appearance, which increases with the amount of post‐deposited Zn. We attribute this to metastable SAT (“sitting atop”) complexes formed by Zn and the macrocycle, that is, an intermediate in the metalation reaction to ZnTCNPP, which occurs upon heating to 500 K. Interestingly, the activation barrier for the successive reaction of the SAT complex to the metalated ZnTCNPP species can also be overcome by a voltage pulse applied to the STM tip.